Initial weight estimation of twin-fuselage configuration in aircraft conceptual design. (January 2023) - Ma, Yiyuan; Yan, Jin; Elham, Ali
The Ultra-High Aspect Ratio Wing (UHARW) concept can improve the aircraft's aerodynamic efficiency and reduce fuel consumption. The Twin-Fuselage (TF) configuration is one of the promising concepts for the UHARW design to reduce the wing bending moments and shear forces. This paper presents the development of a semi-empirical method for the weight estimation of TF aircraft in the initial sizing stage. A physics-based wing weight estimation method is improved for higher fidelity aerodynamic analysis and modified for composite material structures of TF aircraft. This method is used in the design of experiments and the results are applied for regression analysis to establish a semi-empirical method. Eventually, the established semi-empirical weight estimation method is integrated into a TF aircraft conceptual design and performance analysis framework. A mid-range TF aircraft and a long-range TF aircraft are designed and sized to illustrate its application and efficiency in rapidly estimating the TF aircraft weight breakdown.